34 Gender Difference in the Association between Handgrip Strength and Cognitive Performance of Older Adults in Rural Malaysia. (20th December 2019) - Mohan, Devi; Stephan, Blossom C M; Allotey, Pascale; Reidpath, Daniel D
Abstract: Introduction: Handgrip strength is an easy and safe measurement to evaluate the physical functioning of older adults. Lower hand grip strength is associated with cognitive decline, and can be used as an effective method for early detection of cognitive impairment. Objective: This study aimed to evaluate the gender differences in association between hand grip strength and cognitive performance among older adults in rural Malaysia Methods: This was a cross-sectional study done among 200 community dwelling older adults (100 men and 100 women) aged ≥ 50 years. The study was embedded in the ongoing longitudinal study of South East Asia Community Observatory (SEACO) in Segamat district of Johor, Malaysia. Data was collected by trained data collectors during home visits. Cognitive performance was assessed using Mini Mental State Examination (MMSE). Hand grip strength was measured using digital grip dynamometer. Results: The mean age of study participants was 61.5 years (SD= 8.4). Women had lower mean hand grip strength (19.8, SD=5.6) compared to men (33.4, SD= 8.2). The mean MMSE score for women and men were 23 (SD= 4.5) and 25.1(SD=3) respectively. Cognitive impairment was detected in 26% of men and 21% of women. Hand grip strength showed positive association with MMSE score, among women (ß coefficient= 0.302, p<0.001), but not among men (p= 0.077). Hand grip strength was significantly association with MMSE score among women (ß coefficient=0.162, 95% CI = 0.026- 0.298; p=0.02) after controlling for age, level of education and body mass index. Conclusion: The study shows that lower hand grip strength is associated with poor cognitive performance among women, while hand grip strength is not associated with cognitive performance among men.